Capacitação profissional para monitoramento do desenvolvimento infantil: perspectiva do modelo de construção de capacidades centrado na família - Nucci, Larissa Vendramini (2018)
Traditionally, in Brazil, child care has segmented tendencies focused on corrective and rehabilitative actions. However, recent policy proposals that address comprehensive child health care show a positive strategy for monitoring and monitoring child development in the country. In spite of the relevance of the theme, many factors have been mentioned in the national literature as responsible for the gaps in this issue, highlighting the lack of a Brazilian system for monitoring child development that allows the articulation of the sectors for actions to promote integral health of child. Some countries have found answers to this theme, with a model based on individualized practices of support to families, with attention to their needs and priorities through sharing of information, respect for their choices and above all, establish a relationship of partnership between services and family in order to contribute to the construction of family skills to care for their children. The present study aims to evaluate the proposal of a professional training program to monitor child development based on the Family-Centered Capacity Building Model used in Early Intervention programs in Portugal. This is a descriptive and exploratory study, with a qualitative approach. The selected participants are professionals working in the health, education and social assistance sectors in services directed to actions of attention to children's health. The study was developed in three stages. The first proposes the identification of the team and the repertoire of actions and services of the municipality to monitor and monitor child development; the second contemplates the proposal of training of professionals with theoretical and practical knowledge about the Family-Centered Capacity Building Model and the third stage, the evaluation of the repercussions of the proposal of professional training by the participants. The data were collected through a professional identification card, flowchart and scales for evaluation of the training proposal - Likert scale for the evaluation of professional qualification and the Family Service Evaluation Scale in Natural Contexts (Finesse). In the training program, specific instruments of the Model were applied, such as Ecomapa, Routine Based Interview and Individual Plan for Early Intervention. The results obtained in the first stage allowed identifying the services and professionals that compose the municipal team for actions of monitoring DI with families of children at risk of development. The second stage was attended by prof. Dr. Ana Maria Serrano from Minho University, Portugal, and describes in detail the process of training professionals to understand the instruments used in the study model and presents the identification of actions and services to monitor the child development of the municipal child care team. The results of the third stage lead to a satisfactory evaluation of the proposal of professional qualification by the participants and present a comparative analysis of the real and ideal strategies and practices developed in the services, in order to identify how these actions are close to the proposal of the practices centered in the family. It is discussed in the present study how the model studied responds to the needs of a Brazilian municipality with strategies for actions to monitor child development.